The women development fund and the socio-economic empowerment of women in Zimbabwe: a case of Insiza district - Moyo, Simelweyinkosi.Kgompeli (Midlands State University, 2018)
The study’s main aim is to explore the contribution of the Women Development Fund by the Zimbabwean Government on the lives of women. Looking at the marginalisation of women in African countries, Zimbabwe not being an exception there is need for development policies to ensure the empowerment of women so that they participate in reviving the country’s economy. This study was carried out in Insiza District, where qualitative research approach was applied through the use of interviews and questionnaires. Findings showed that the Women Development Fund is effective on its agenda for empowering women. The study also revealed that there is no legal framework governing the operation of the fund. Recommendations were made to The Ministry of Women Affairs, Gender and Community Development for them to facilitate beneficiaries of the fun with trainings on how to utilise the fund and also about the legal framework guiding its operation.